LA DINÁMICA ISOTÓPICA COMO FUNDAMENTO DEL DISCURSO ARTÍSTICO MÚSICO-LITERARIO - González Martínez, Juan Miguel (Imafronte, 1997)
This paper is integrated in the field of the study of heterosemiosis, defined by the author previously, and centred in a specific aspect of the semiotic functioning of the artistic manifestations that integrate musical and literary elements. Using the greimasian concept of isotopy to explain the possibilities that are considered in the integration , in a coherent unitary textual structure, of the different elements that constitute the musical-literary discourse, to the extent that they can be considered in relation to certain isotope coordinales of reference, that are defined by a series of disotopical-isotopes operators. From this perspective, attention is given to the way in which diverse disfunctions, that take place in the discursive process in the form of successive processes of engage-disengage. define the textual structure and determine the processes of the generation of meaning in the discourse. Once the specific field has been considered that defines the heterosemiotic musical-literary discourse. the temporal, spacial and above all the acting disfunctions receive a special attention.